2012
DOI: 10.1088/2041-8205/762/2/l30
|View full text |Cite
|
Sign up to set email alerts
|

Clash: The Enhanced Lensing Efficiency of the Highly Elongated Merging Cluster Macs J0416.1–2403

Abstract: We perform a strong lensing analysis of the merging galaxy cluster MACS J0416.1−2403 (M0416; z = 0.42) in recent CLASH/HST observations. We identify 70 new multiple images and candidates of 23 background sources in the range 0.7 z phot 6.14 including two probable high-redshift dropouts, revealing a highly elongated lens with axis ratio 5:1, and a major axis of ∼100 (z s ∼ 2). Compared to other well-studied clusters, M0416 shows an enhanced lensing efficiency. Although the critical area is not particularly larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
205
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 187 publications
(220 citation statements)
references
References 52 publications
12
205
0
Order By: Relevance
“…In addition, we do not find any convincing counterimage (third image of a triple 'fold' configuration) for systems 14, 15, and 18. Zitrin et al (2013) presented a strong-lensing model with 23 systems identified in this cluster in the new CLASH (Postman et al 2012) data, producing in total 70 images. Due to the very elongated nature of the cluster mass distribution (Fig.…”
Section: Abell 2744mentioning
confidence: 99%
“…In addition, we do not find any convincing counterimage (third image of a triple 'fold' configuration) for systems 14, 15, and 18. Zitrin et al (2013) presented a strong-lensing model with 23 systems identified in this cluster in the new CLASH (Postman et al 2012) data, producing in total 70 images. Due to the very elongated nature of the cluster mass distribution (Fig.…”
Section: Abell 2744mentioning
confidence: 99%
“…is a Light Traces Mass (LTM) method, so that both the galaxies and the dark matter follow the light distribution. The method is described in detail by Zitrin et al ( , 2013, and it is inspired by the LTM assumptions outlined by Broadhurst et al (2005). The model consists of two main components.…”
Section: Description Of the Inference Process And Error Estimationmentioning
confidence: 99%
“…Finally, individual galaxies can be assigned with free masses to be optimized by the minimization procedure, to allow more degrees of freedom deviating from the initial imposed LTM. This procedure has been shown to be very effective in locating multiple images in many clusters (e.g., Zitrin et al , 2012bZitrin et al , 2013Zitrin et al , 2015, even without any multiple images initially used as input (Zitrin et al 2012a). Most of the multiple images in MACSJ1149.5+2223 that were found by Zheng et al (2012) were identified with this method.…”
Section: Description Of the Inference Process And Error Estimationmentioning
confidence: 99%
“…In the NFW model, instead of smoothing the galaxy distribution to obtain the cluster-wide component, the latter is represented with elliptical NFW density profiles, following Navarro, Frenk & White (1997). The best fit solution and accompanying errors are estimated via a long MCMC; see Zitrin et al (2013) for further details.…”
Section: Zitrinmentioning
confidence: 99%